Francis L. Moore letter to Thomas H. Kent regarding bird sightings, July 31, 1980 - Moore, Francis L.et al (1980)
Field notes contributed by Francis L. Moore in a letter to Thomas H. Kent July 31, 1980 with observer Robert K. Myers. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1980 Epson - sheet feed/flatbed